Language Politeness in the Javanese Verb Speech Level - Dwi Atmawati (Lingua Cultura, 2021)
The research aimed to observe the use of Javanese verb forms using a sociolinguistic approach. The object of the research was the selection of Javanese verb forms used by speakers in the Magelang region. The informants were children, adolescents, and adults, both male and female. The informants were 50 Javanese speakers. Data were obtained by the technique of listening, recording, and taking notes. The problem was studied using speech component theory and language politeness norms. The research applied a qualitative descriptive method. The result indicates that some children and the younger generation are less able to choose the correct form of verbs related to the level of speech, for example, the words ‘siram’ (bath), ‘tindak’ (go), and ‘mireng’ (hear). These three words should refer to people with whom to speak and be respected, not to describe oneself. Using an inaccurate form of the verbs can lead to an assumption that the speaker is impolite. Based on the findings of the research, it is hoped that there will be efforts, both in the domain of families, schools, stakeholders, and policymakers, to provide better education to speakers, especially children, and the younger generation. With better education, it is hoped that the younger generation will be able to understand well the proper use of verbs. Incorrect use of the verb form can indicate the impoliteness of the speaker.